Autonomy and respect during maternity care among postnatal mothers in a tertiary level hospital. - Adhikari,Shila (2019)
ABSTRACT: Lack of respectful maternity care (RMC) act as more powerful deterrents to skilled birth care utilization than other more commonly recognized deterrents such as geographic and financial obstacles. Ensuring high level of RMC encourage the women to utilize facility based care, which is essential for improving maternal and neonatal health. Thus the objective of the study is to find out autonomy and respect during maternity care among the postnatal mothers in a tertiary level hospital. A descriptive cross - sectional study was conducted among 214 postnatal mothers receiving child birth services from maternity ward and birthing centre were selected by using non-probability purposive sampling technique. Data was collected from face to face interview using structured interview schedule in four weeks duration. Analysis of data was done by using descriptive statistics (number, percentage, mean, standard deviation) and chi- square test was used for association between autonomy and respect and selected socio-demographic variables. The study result indicated that (74.8%) of the respondents had high level of autonomy. Similarly, (71%) of the respondents reported that they experience high level of respect. A significant association was present between autonomy of postnatal mothers with caste (p=.027) and parity (p=.005) and a significant association was present between respect of postnatal mothers with type of delivery is with p value (.001). Hence, level of autonomy and respect tends to be high among postnatal mothers during maternity care and is associated with caste, parity and type of delivery. Continuous professional development programme for all cadres of health personnel should be conducted in respectful maternity care of maternity ward. Keywords: Autonomy, Respect, Postnatal mothers